Answer:
Explanation:
2) 3x + 5y = 15
divide by 15;
3x/15 + 5y/15 = 15/15
x/5 + y/3 = 1
x-intercept= 5
y-intercept= 3
6) 3x -y = 14
-y = - 3x + 14
divide by (-) ; y = 3x -14 { y = mx +c}
slope= 3 & y-intercept= -14
7)2x - 8y =32
-8y = -2x +32
divide by (-8)
-8y/-8 = -2x/-8 + 32/(-8)
y = x/4 - 4
slope = 1/4 ; y-intercept = -4
11) (0,3) ;(2, -5)
m = y₂ - y₁ / x₂ - x₁
m = -5 - 3 / 2-0
= -8/2
m = -4
Equation:
y - y₁ = m (x- x₁)
m = -4 ;(0,3) { you can take any of this two point}
y - 3 = -4 (x - 0)
y - 3 = -4x
y = -4x + 3
slope = -4 ;Y-intercept = 3
14) 5x = 15 + 3y
5x - 3y = 15
5x/15 - 3y/15 = 15/15 {divide by 15}
x/3 + y/ -5 = 1
x-intercept = 3
y-intercept = -5
18) 5y + 3x = 10
5y = -3x + 10
5y /5 = -3x/5 + 10/5 {divide by 5}
y = -3x/5 + 2
slope= -3/5 ; y-intercept = 2
24) (-5,-4) ; (15,0)
m = y₂ - y₁ / x₂ - x₁
= 0 - (-4) / 15 - (-5) = 4/15+5 = 4/20
m = 1/5
Equation:
y - y₁ = m (x- x₁)
m = 1/5 ;(15,0) { you can take any of this two point}
y - 0 = 1/5 (x - 15)
y = 1/5x - 15/5
y = 1/5x - 3
slope = 1/5 ; y intercept = -3